Penerapan Metode SAS (Struktural Analitik Sintetik) Untuk Meningkatkan Kemampuan Membaca Permulaan di Kelas II SDN 235/VI Tanjung Mudo II - Ermanias, Ermanias; Hidayat, Puput Wahyu (CV. Master Literasi Indonesia, 2025)
This study aims to improve the early reading skills of second-grade students at SDN 235/VI Tanjung Mudo II through the application of the SAS Method (Structural Analytic Synthetic). This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were one teacher and 15 students. The results showed an improvement in the teacher's teaching process from 69% in Cycle I to 100% in Cycle II. Student participation increased from 68% to 82%. The early reading test results also improved, with 60% of students achieving mastery in Cycle I, rising to 87% in Cycle II. Therefore, the SAS method proved effective in enhancing students' early reading skills